The intersection of bisexuality and gender modality: Exploring differences in sexual interest and satisfaction. - Soros, Jenn J.; Fuller, Kimberly A.; Sargent, Caleb (International Journal of Transgender Health)
Background: Sexual well-being is crucial for overall health, but research on bisexual individuals' sexual experiences across gender modalities is limited. This study aims to address this gap by examining differences in sexual interest and satisfaction among bisexual adults of various gender modalities. Objectives: To investigate whether there are differences in sexual interest and satisfaction levels among bisexual adults across gender modalities (cisgender men, cisgender women, and transgender/gender diverse individuals). Methods: A cross-sectional online survey was conducted with 475 self-identified bisexual adults (161 cisgender men, 228 cisgender women, 86 transgender/gender diverse). Participants completed demographic questionnaires and standardized measures of sexual interest and satisfaction from the PROMIS Sexual Function and Satisfaction Version 2.0. One-way ANOVAs were used to compare scores across gender modality groups. Results: Significant differences were found in sexual interest across gender modalities (F(2, 472) = 10.131, p <.001). Cisgender men reported higher sexual interest (M = 52.958) compared to cisgender women (M = 48.563, p <.001) and transgender/gender diverse individuals (M = 50.566, p =.170). No significant differences were found in sexual satisfaction across gender modalities (i(2, 387) = 2.102, p =.124). Conclusions: While cisgender bisexual men reported higher levels of sexual interest, sexual satisfaction was comparable across all gender modalities. These findings highlight the need for nuanced understanding of sexual experiences among bisexual individuals and underscore the importance of considering gender modality in research and clinical practice related to sexual health. Implications: This study contributes to the limited research on bisexual individuals' sexual experiences across gender modalities. The findings can inform more inclusive and tailored approaches to sexual health care and support for bisexual individuals of all gender modalities.